2023
DOI: 10.1002/agg2.20361
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen‐year stover harvest and tillage effects on soil compaction in Iowa

Abstract: Corn (Zea mays L.) stover is an abundant biomass source with multiple end‐uses including cellulosic biofuel production. However, stover removal may increase soil compaction by reducing organic matter inputs and increasing vehicle loads during harvest. While numerous studies have reported stover removal impacts on soil physical quality, few have assessed the role played by traffic compaction. Our objective was to quantify subsurface soil compaction after 13 years of chisel plow versus no‐till management and no,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Subsequent studies at these sites found that hybrid selection and intensive crop management can minimize the CMYP (Vogel & Below, 2018), and that enhancing residue decomposition could further reduce the CMYP (Vogel & Below, 2019). Studies that utilized residue removal as a management strategy reported CM yield increases of 4.1% (Karlen et al, 2014), 9% (Phillips et al, 2023), and 0.0% or 12.0% when tilled and −10.3% or 9.2% without tillage (Coulter & Nafziger, 2008).…”
Section: Continuous Maize Yield Penaltymentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies at these sites found that hybrid selection and intensive crop management can minimize the CMYP (Vogel & Below, 2018), and that enhancing residue decomposition could further reduce the CMYP (Vogel & Below, 2019). Studies that utilized residue removal as a management strategy reported CM yield increases of 4.1% (Karlen et al, 2014), 9% (Phillips et al, 2023), and 0.0% or 12.0% when tilled and −10.3% or 9.2% without tillage (Coulter & Nafziger, 2008).…”
Section: Continuous Maize Yield Penaltymentioning
confidence: 99%
“…The removal of maize stover at or following harvest has been shown to enhance yields of CM when compared to no removal of these residues (Karlen et al, 2014;Phillips et al, 2023). Crop residue loads can be reduced by practices such as burning, removal through baling, and intensive tillage (Beri et al, 1995;Chen et al, 2019;Freebairn & Boughton, 1985), but these practices may negatively influence the inherent soil fertility levels, soil structure, and the associated soil microbial communities, as well as decrease soil carbon stocks (Blanco-Canqui & Lal, 2009;Jin et al, 2015;Phillips et al, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation